Implementasi Unsur Informasi dan Komunikasi dalam Mendukung Pencegahan Fraud : Analisis Penerapan SPIP di Inspektorat Daerah Kabupaten Bone Bolango - Dungi, Annisa; Mattoasi, Mattoasi; Wuryandini, Ayu Rakhma (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study wants to examine the effect of company size, leverage, and liquidity to the profitability of pharmaceutical companies in Indonesia. The population of this research is all pharmaceutical companies listed in Indonesia Stock Exchange in 2019 to 2023. This sampling method used non-probability sampling particularly purposive sampling. Out of the entire population 12 companies, ten companies met the criteria. The data analysis technique used multiple linear regression processed by application SPSS version 25. The result shows that company size and liquidity have a significant effect on ROA and ROE, Leverage has a significant effect on roa. The research model is able to describe the performance of profitability amounting to 35.5 % roa or for return in equity 20.8 %. We suggest that next research enquiries on all sectors can enlarge the sample by adding other variable as cost structure and innovation. It is expected with this approach to add to the emphasis of the results.